KIPUTZ IX: UN CONJUNTO SINGULAR DE CIERVO ROJO (CERVUS ELAPHUS LINNAEUS, 1758) DEL PLEISTOCENO SUPERIOR DE LA PENÍNSULA IBÉRICA (Ameghiniana, 2014)
Kiputz IX is an upper Pleistocene site that has provided the richest set of Cervus elaphus complete remains in the Iberian Peninsula. This paper provides a metric and isotopic study of the postcranial skeleton of the 43 individuals that conform this tafocenosis. The robustness of the distal metacarpus evidences the existence of a clear sexual dimorphism and a small predominance of females respect to males. The stage of dental substitution makes evident that the sample is dominated by sub-adult and juvenile specimens, with a low proportion of juvenile and adult individuals. Application of a variability size index on a group of samples from the middle and upper Paleolithic in the Cantabrian Region do not allow establishing any osteometric relation with geographic and chronological factors. Variations in ? C values among red deer and reindeer are related to the specialized consumption of different plant types. However, the gradual decline in red deer ?13 C values over time may reflect the so-called ‘canopy effect’ impacting the floristic composition. Variations in the ?13 C and ?15 N values, studied together in red deer show that when climatic conditions were more temperate, humidity was higher in this environment than in de northern Pyrenees. The red deer sample from Kiputz IX constitutes a good basis for comparative studies of red deer populations from the Middle and Upper Pleistocene of Europe.